Pelatihan Pembuatan Media Pembelajaran dengan Powerpoint Guna Mendukung Pembelajaran Berbasis Permainan di Sekolah Dasar - Satri Asriyanti; Fatmawati; Rahim, Abdul (Indonesian Journal of Education and Community Services, 2025)
Digital transformation in education requires elementary school teachers to have the skills to design interactive, game-based learning media. This community service activity aims to empower teachers through intensive training and mentoring in creating PowerPoint-based learning media integrated with game-based learning principles. The training consisted of four main sessions covering digital literacy, utilizing PowerPoint features, designing game elements, and interactive media simulations and demonstrations. The results of the activity demonstrated an increase in teacher competency, with an average score increase of 40–50% from pre-test to post-test. All participants successfully produced interactive learning media, and a satisfaction rating of 4.6/5. This program also encouraged the formation of teacher learning communities and the continued development of innovative learning media. This activity had a positive impact on improving teacher digital literacy and student engagement in learning, and has the potential to be replicated in other schools.